Effect of temperature and duration of thermal pasteurization on polyphenol oxidase (PPO) enzyme activity, total plate count (TPC), physicochemical and organoleptic properties of Cavendish banana fruit juice (Musa cavendishii) - Bambang Dwi Argo; Cici Damayanti; Anik Wulandari; Umi Mianadhiroh (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
This research aims to determine the effect of temperature and duration of thermal pasteurization process in Cavendish banana juice. Cavendish banana is an abundant cultivated banana that has not been used properly, which is a climacteric fruit that has increased ethylene production after harvesting. Cavendish bananas have great potential as fruit juice. Pasteurization was carried out at temperatures of 55, 60, 65, 70 and 75 ℃ for 5, 10, and 15 minutes. Pasteurization with higher temperature and time can increase the total dissolved sugar and viscosity as well as decrease the pH value and PPO enzyme activity. The reducing sugar content of Cavendish banana juice was determined using the DNSA method with the greatest value at 55 ℃ for 5 minutes, which is 9.53%. Meanwhile, the content of phenol and flavonoid was determined using the Krishnan and Sinija method. The highest value of phenol and flavonoid content at 60 ℃ for 5 minutes, was 0.1728 mg GAE/g and 0.1583 mg QE/g sample. Antioxidant activity was determined using the DPPH method and the greatest percentage of inhibition at 60 ℃ for 5 minutes, which is 61.60%.  Vitamin C levels were identified by the UV-Vis spectrophotometry method with the greatest value at 55 ℃ for 5 minutes, which is 1.1409  mg /100 g. The Total Plate Count (TPC) of Cavendish banana juice decreased after pasteurization with the smallest total number of bacteria  at 75 ℃ for 15 minutes, with a value of 3.2×101 CFU/ml. Pasteurization process at 75 ℃ for 15 minutes can reduce the activity of PPO enzyme as much as 97%. In the organoleptic test, preferred level of Cavendish banana juice to all attributes of the average hedonic scale with the category of the likes.